EVALUATION OF HEPATIC MASS LESIONS BY DIFFUSION WEIGHTED MAGNETIC RESONANCE IMAGING - PONNADA, CHANDRA SEKHAR; SINGH, HARPREET; SHUKLA, RAJAT; HEER, ARVINDER KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The purpose of this study was to compare apparent diffusion coefficient (ADC) values for benign and malignant neoplastic hepatic lesions and also for suspected infective hepatic masses in which histopathology may always not be indicated. Methods: This is a cross-sectional study conducted in the department of radio diagnosis and imaging, army hospital research and referral, Delhi Cantt. All the patients coming for magnetic resonance imaging (MRI) scans for focal liver lesions detected on other imaging modalities were included. The imaging was done at the 1.5 Tesla MAGNETOM AVANTO A Tim system (Siemens Ltd.). Various parameters of the morphology of lesions in conventional MRI and parameters in diffusion-weighted MRI were evaluated. Results: A total of 75 patients were included in the study. The mean age of the subjects was 52.57±15.28 years, with a male: female sex ratio of 0.5:1. Among the 75 subjects, 20 subjects with hepatic cysts had no restrictions, and 12 patients with hemangioma were hyperintense on both diffusion-weighted imaging (DWI) and ADC. The mean differences between benign and malignant lesion ADC values. The difference was statistically significant (p<0.001). In the present study, we get a cut-off for the ADC value of 1.581×10-3 mm2/s, which proved to be an optimal parameter for differentiation between benign and malignant lesions. Conclusion: DWI proved to be a very useful supplementary imaging technique in conjunction with conventional imaging sequences in the analysis of focal hepatic lesions and should be included in the imaging algorithm for such lesions.